2016
DOI: 10.2176/nmc.oa.2016-0102
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Drip, Ship, and Retrieve Paradigm for Acute Ischemic Stroke: a Single Center Experience

Abstract: This study analyzed the efficacy and safety of the “drip, ship, and retrieve (DSR)” approach used to improve patient access to thrombectomy for acute stroke. Methods: The study participants were 45 patients who underwent thrombectomy following intravenous tissue plasminogen activator between September 2013 and August 2015. Patients were divided into two groups according to whether they were transferred from another hospital (DSR group; n = 33) or were brought in directly (Direct group; n = 12). The two groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
(13 reference statements)
0
22
0
1
Order By: Relevance
“…The patient can be given intravenous thrombolytic treatment in the ambulance and transported to the appropriate stroke center. articles included in qualitative analysis 9 articles included in quantitative analysis 28,[30][31][32][33]35,[37][38][39] 18 articles excluded from quantitative analysis: -one organizational model only 25,34 -models used intravenous thrombolytic treatment only (no intra-arterial treatment) 15,17,18,20,22,23 -models used different recanalisation treatments 16,21 -no information about clinical outcome 13,14,19,24,26,27,29,34,36,51 International Journal of Stroke, 14(1) The mother-ship model was used for the majority of the patients in the completed randomized-controlled trials of intra-arterial treatment. 21,[26][27][28] The observational studies showed that the drip-and-ship model is frequently used in clinical practice in many countries (United States, South Korea, Spain, Germany, Italy, and France), whereas there were few reports of the mobile stroke unit and the mobile interventionist models in the medical literature.…”
Section: Characteristics Of the Different Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient can be given intravenous thrombolytic treatment in the ambulance and transported to the appropriate stroke center. articles included in qualitative analysis 9 articles included in quantitative analysis 28,[30][31][32][33]35,[37][38][39] 18 articles excluded from quantitative analysis: -one organizational model only 25,34 -models used intravenous thrombolytic treatment only (no intra-arterial treatment) 15,17,18,20,22,23 -models used different recanalisation treatments 16,21 -no information about clinical outcome 13,14,19,24,26,27,29,34,36,51 International Journal of Stroke, 14(1) The mother-ship model was used for the majority of the patients in the completed randomized-controlled trials of intra-arterial treatment. 21,[26][27][28] The observational studies showed that the drip-and-ship model is frequently used in clinical practice in many countries (United States, South Korea, Spain, Germany, Italy, and France), whereas there were few reports of the mobile stroke unit and the mobile interventionist models in the medical literature.…”
Section: Characteristics Of the Different Modelsmentioning
confidence: 99%
“…A total of nine studies 28,[30][31][32][33]35,[37][38][39] reported outcomes of patients treated with intra-arterial therapy under different models, and were included in the quantitative analysis. The studies included a total of 4127 patients, from eight observational studies 28,[30][31][32][33]35,[37][38][39] and one randomized-controlled trial of intra-arterial therapy. 28 All studies compared the mother-ship and the dripand-ship models, and Figure 2 presents data on the process performance of these models.…”
Section: Process Performance and Clinical And Radiological Outcomes Umentioning
confidence: 99%
“…Systematic search retrieved 18 studies including 7,017 patients (PRISMA flowchart) ( Figure 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Most of the included studies were observational and prospective, only one study was a RCT 15 (Table 1). As a result, quality of studies ranged fair to good, with only one RCT achieving optimal score on risk of bias assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Other previous studies have reported the safety and effectiveness of the DSR approach in AIS. 7,21) In this study, seven patients living on the islands were treated via the DSR method; of these, three patients had favorable outcomes, and four of seven patients transported via the DSR method in the Islands group had successful reperfusion (Table 3).…”
Section: Discussionmentioning
confidence: 85%